Vertebral artery dissection in relation to pregnancy: a case series and literature review - Kendal F. Rosalik, DO; Logan M. Havemann, MD; Morgan E. Wasickanin, MD; Jill A. McCaulley, MD; Sarah M. Edwards, MD; Katherine M. Leonard, DO (Elsevier, 2023)
Cervical artery dissection is an uncommon condition for which pregnancy and postpartum states confer increased risk. Although the majority of patients with this condition fully recover, including resolution of the dissection on imaging, long-term sequelae include a variety of cardiovascular conditions that may be associated with high rates of morbidity and mortality. Here, we review 2 cases of vertebral artery dissection in relation to pregnancy. Our first case will review the management of a pregnant patient with a history of vertebral artery dissection; whereas our second case reviews a presentation of postpartum vertebral artery dissection. Providers should maintain a high suspicion of cervical artery dissection in pregnant and postpartum patients presenting with headache and neck pain.